1995
DOI: 10.1620/tjem.175.43
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Ammonia and Carnitine Levels in Short-Term Treatment with Pivalic Acid-Containing Prodrug.

Abstract: We investigated the influence on mitochondrial functions in carnitine deficiency caused by short-term treatment of cefterampivoxil (CFTM-PI) which is one of pivaloyloxymethyl-esterified antibiotics in adult volunteers and diseased children. Administration of CFTM-PI caused hypocarnitinemia in all cases, and we observed a significant elevation of blood ammonia levels compared with those after its withdrawal in diseased children. A significant negative correlation was found between the levels of serum free carni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…However, a case has been reported of a 1-year-old Japanese patient with hypoglycemia associated with hypocarnitinemia induced by 2 days of cefcapene pivoxil treatment [12]. Additionally, Ito et al reported that treatment with cefteram pivoxil significantly decreased the level of serum free carnitine in both children and adults, even in short-term therapy, and advised that carnitine supplementation may be necessary for patients who are taking these antibiotics, particularly those vulnerable to carnitine deficiency [13]. Although our patient was an older child who could usually receive adequate calories orally (1200 kcal/day, appropriate for her body weight and activity level), she did not receive enough to eat for 3 days (about half of her usual calorific intake) after antibiotic treatment was initiated because of her acute pharyngitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, a case has been reported of a 1-year-old Japanese patient with hypoglycemia associated with hypocarnitinemia induced by 2 days of cefcapene pivoxil treatment [12]. Additionally, Ito et al reported that treatment with cefteram pivoxil significantly decreased the level of serum free carnitine in both children and adults, even in short-term therapy, and advised that carnitine supplementation may be necessary for patients who are taking these antibiotics, particularly those vulnerable to carnitine deficiency [13]. Although our patient was an older child who could usually receive adequate calories orally (1200 kcal/day, appropriate for her body weight and activity level), she did not receive enough to eat for 3 days (about half of her usual calorific intake) after antibiotic treatment was initiated because of her acute pharyngitis.…”
Section: Discussionmentioning
confidence: 99%
“…Valerylcarnitine (C5‐N) accumulates due to metabolic disorders involving fatty acids with odd‐numbered carbon chains, and 2‐methylbutyrylcarnitine (C5‐M) and isovalerylcarnitine (C5‐I) accumulate due to disorders involving isoleucine and leucine, respectively. Furthermore, pivaloylcarnitine (C5‐P) is formed when patients are treated with antibiotics modified by the pivoxyl group 7, 8. All these C5s are indistinguishable using the current MS/MS methodology.…”
mentioning
confidence: 99%
“…The maximum C5-acylcarnitine blood concentration was reached 4 hours after balm ingestion in all volunteers. Considering that the pivalic acid derivative neopentanoic acid conjugates the free carnitine [4][5][6] and that the breast-feeding period could be quite long (generally some months), we cannot exclude a potentially dangerous secondary carnitine deficiency due to a long-term nipple fissure balm application. Exogenous unusual long-term pivalate exposure from pivalic esters of antibiotics to mothers or newborns had previously been reported as responsible for carnitine depletion and hypoglycemic convulsions.…”
Section: Resultsmentioning
confidence: 99%